Strengthening the Capacity of Tourism Awareness Groups through Eco-Friendly Souvenir Diversification in Geosite Ngingrong, Gunungkidul: Penguatan Kapasitas Pokdarwis melalui Diversifikasi Souvenir Ramah Lingkungan di Geosite Ngingrong, Gunungkidul - Kuntum Febriyantiningrum; Tatag Bagus Putra Prakarsa; Rizka Apriani Putri; Himmatul Hasanah (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Geosite Ngingrong in Gunungkidul Regency is a karst landscape with significant potential for ecotourism and local creative economy development. However, limited product diversification and institutional capacity of the Tourism Awareness Group (Pokdarwis) constrain the integration of natural resources into sustainable economic value. This community service program aimed to strengthen the capacity of Pokdarwis Bangun Kencana through training on environmentally friendly souvenir diversification based on locally sourced natural materials. The program employed a participatory training approach integrating conceptual knowledge enhancement, technical skill development, eco-aesthetic design innovation, and basic marketing strategies. The results indicate a 42% average increase in participants’ knowledge, as measured by pre-test and post-test evaluation, and the development of several prototype products reflecting local aesthetics and conservation values. Beyond technical improvement, the program enhanced entrepreneurial motivation and environmental awareness. Conceptually, this initiative contributes an integrative model linking creative economy, eco-aesthetic product design, and community-based ecotourism as a strategy for sustainable village tourism development.